Approaches to notation for embodied engagement with a novel neural network-based musical instrument - Bacon, Benjamin Keith; Auri, Leonardo; McKee, Holly Ambrozic (Frontiers in Computer Science, 2025)
IntroductionThe growing complexity and breadth of sonic possibilities enabled by sound synthesis technologies give rise to significant challenges for the notation of music, especially in light of emerging neural network-based paradigms. Prescriptive vs. descriptive notation has emerged as a paradigm with relevance to this challenge.MethodsExperienced musicians (n = 11) were asked to compose for a novel neural network-based digital musical instrument and were prompted to produce descriptive and prescriptive graphic notations.ResultsGroup differences in task conceptualisation were observed, while further analysis revealed perpendicular dimensions of variation in the resulting musical notation, which were associated with perceived creativity support.DiscussionBased on this analysis, a conceptual framework is proposed that suggests useful strategies for music composition and creative endeavours.SummaryBeyond the representation of sound and/or action, use of abstraction and metaphor emerge as strategies for music notation, with consequences for support of creative work.